Persepsi Taruna Dan Dosen Terhadap Pembelajaran Jarak Jauh Metode Daring - Nursyam; Oktavera Sulistiana; Sarce Sampe Bungin (Politeknik Pelayaran Barombong, 2021)
The purpose of this study was to determine the perceptions of cadets and lecturers' perceptions of distance learning online methods at the Barombong Shipping Polytechnic. Distance Education (PJJ) is conceptually seen from two aspects, namely the institutional aspect and the personal aspect. The existence of the covid outbreak that has hit our country in Indonesia requires us to do distance learning using online methods. This study uses a qualitative approach. Bogdan and Taylor in Moleong, describe, qualitative research is research that produces descriptive data in the form of written or spoken words from people and observable behavior. The data analysis technique was based on the research objective, namely knowing the cadets' perception of distance learning at the Barombong Shipping Polytechnic. Therefore, the data analysis technique used was descriptive analysis. Data collection techniques were carried out using questionnaires and documentation. The results showed that cadets' perceptions of distance learning online methods were seen from several aspects, namely, aspects of the availability of IT and support, aspects of lecturers, aspects of the ability to use IT, aspects of ease of understanding subject matter and aspects of cadets' motivation to learn through online learning. positive. Lecturers/instructors' perceptions of distance learning online methods when viewed from several aspects including, aspects of the preparation carried out by the institution, the activity of cadets, the ability to make On-line-based learning materials and the ability to use IT, indicate that the perception is positive although there are still some aspects which needs to be fixed